2018
DOI: 10.2217/fmb-2018-0234
|View full text |Cite
|
Sign up to set email alerts
|

The CRISPR-cas System Promotes Antimicrobial Resistance in Campylobacter Jejuni

Abstract: Aim: The purpose of current study is to find out relationship between cas9 gene and antimicrobial resistance in Campylobacter jejuni NCTC11168. Materials & methods: The involvement of the cas9 gene in antimicrobial resistance of C. jejuni was determined by assessment of minimum inhibitory concentration, clustered regularly interspaced short palindromic repeats (CRISPR)-cas gene expression in standard strains, in vitro resistance development and transcriptome analysis of a cas9 deletion mutant and wild stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 41 publications
4
31
0
2
Order By: Relevance
“…Searches were conducted against all bacteria, and alignments having an E-value below the cut-off value with similarity greater than 80% were selected. Therefore, alignment search criteria were eventually based on sequence identity and E-value [25,59]. The repeat regions identified by the program were aligned using MEGA X [60] to evaluate their conservation.…”
Section: Detection Of Crispr Array and Analysis Of Crispr Spacersmentioning
confidence: 99%
“…Searches were conducted against all bacteria, and alignments having an E-value below the cut-off value with similarity greater than 80% were selected. Therefore, alignment search criteria were eventually based on sequence identity and E-value [25,59]. The repeat regions identified by the program were aligned using MEGA X [60] to evaluate their conservation.…”
Section: Detection Of Crispr Array and Analysis Of Crispr Spacersmentioning
confidence: 99%
“…Watson et al found that CRISPR‐Cas can inhibit HGT by preventing transformation and conjugation, but it usually enhances the transduction process and thus plays a different role in different pathways of HGT. Shabbir et al found that Campylobacter jejuni NCTC11168, the cas9 gene of which was knocked out, was more sensitive to some antibiotics than before, and they arrived at the conclusion that CRISPR‐cas9 gene plays a role in the regulation and enhancement of antimicrobial resistance. Bacteria can inactivate the CRISPR‐Cas system through a variety of mechanisms in the face of high antibiotic stress, such as the loss of integrity of the CRISPR‐Cas system, containing a transposable element in the cas gene, and the loss of the function by single nucleotide substitutions or deletions of cas gene .…”
Section: Introductionmentioning
confidence: 99%
“…J Lit Pharm Sci. 2020;9(1): [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] Huntington hastalığı (HD), mutant proteinin dominant kalıtım ile hastalığa neden olduğu birçok genetik bozukluktan biridir. HD mutasyonu, Huntingtin geninde (HTT), çok sayıda (35'ten fazla) CAG dizisi tekrarı olan kişilerde görülmektedir.…”
Section: Geneti̇k Hastaliklarunclassified
“…Shabbir ve ark., Campylobacter jejuni NCTC 11168'de Cas9 geni ve antimikrobiyal direnç arasındaki ilişkiyi bulmayı amaçladıkları çalışmada, Cas9 geninin Campylobacter jejuni'nin antimikrobiyal direncine katılımını, minimum inhibitör konsantrasyonunu, standart suşlarda CRISPR-Cas gen eks-presyonunu ve in vitro direnç gelişimini bir cas9 delesyon mutantının ve yabanıl suşların transkriptom analizinin değerlendirilmesiyle belirlemişlerdir. 64 Standart suşlarda CRISPR ile ilişkili genlerin artan ekspresyonunu ve cas9 mutant suşunun antibiyotiklere karşı vahşi suştan daha duyarlı olduğunu gözlemlemişlerdir. Transkriptom analizinde, cas9 geninin, C. jejuni'de antimikrobiyal direnci artırmak için birkaç geni düzenlediği ortaya konmuş ve CRISPR-Cas sisteminin C. jejuni'de antimikrobiyal direncin artırılmasında rol oynadığı bildirilmiştir.…”
Section: Anti̇mi̇krobi̇yal Ajanlarunclassified